The Impact of a Post-Prescription Review and Feedback Antimicrobial Stewardship Program in Lebanon - Anita Shallal; Chloe Lahoud; Dunia Merhej; Sandra Youssef; Jelena Verkler; Linda Kaljee; Tyler Prentiss; Seema Joshi; Marcus Zervos; Madonna Matar (MDPI AG, 2022)
Antimicrobial stewardship programs (ASPs) are effective means to optimize prescribing practices. They are under-utilized in the Middle East where many challenges exist for ASP implementation. We assessed the effectiveness of infectious disease physician-driven post-prescription review and feedback as an ASP in Lebanon. This prospective cohort study was conducted over an 18-month period in the medical, surgical, and intensive care units of a tertiary care hospital. It consisted of three phases: the baseline, intervention, and follow-up. There was a washout period of two months between each phase. Patients aged ≥16 years receiving 48 h of antibiotics were included. During the intervention phase, the AMS team reviewed antimicrobial use within 72 h post-prescription and gave alternate recommendations based on the guidelines for use. The acceptance of the recommendations was measured at 72 h. The primary outcome of the study was days of therapy per 1000 study patient days. A total of 328 patients were recruited in the baseline phase (August-October 2020), 467 patients in the intervention phase (January-June 2021), and 301 patients in the post-intervention phase (September-December 2021). The total days of therapy decreased from 11.46 during the baseline phase to 8.64 during the intervention phase (p < 0.001). Intervention acceptance occurred 88.5% of the time. The infectious disease physician-driven implementation of an ASP was successful in reducing antibiotic utilization in an acute care setting in Lebanon.